Survival estimation of melanoma patients with brain metastasis using the Melanoma-molGPA score: external validation from a French cohort. Issue 5 (October 2020) - Dalmasso, Céline; Pagès, Cécile; Chaltiel, Léonor; Brun, Aurore; Sibaud, Vincent; Boulinguez, Serge; Chira, Ciprian; Moyal, Elizabeth; Lubrano, Vincent; Meyer, Nicolas; Modesto, Anouchka
Abstract : While immunotherapies and targeted therapies such as BRAF inhibitors have improved the prognosis, BM is still associated with poor outcome and a short survival. Metastatic melanoma patients are a heterogeneous subgroup with variable prognosis. As several prospective clinical trials have addressed the question of optimal therapy for these patients, an accurate validated selection tool is needed. Melanoma molecular graded prognostic assessment (Melanoma-molGPA) is a new prognostic score for BM melanoma patients. We decided to perform an external validation of this score. All consecutive patients treated between May 2014 and December 2017 for a newly diagnosed locally advanced or metastatic melanoma with available status for BRAF mutation were identified. Melanoma mol-GPA was applied in each patient with BM and correlated to overall survival. One hundred patients were included. Median follow-up was 27.8 months. Distribution for the Melanoma-molGPA groups GPA 0–1, GPA 1.5–2, GPA 2.5–3 and GPA 3.5–4 were as follows: 23, 51, 24 and 2.0%, respectively. Subgroups GPA 2.5–3 and 3.5–4 were combined. Median overall survival for groups GPA 0–1, 1.5–2 and 2.5–4.0 was 4.2, 6.9 and 18.4 months, respectively, P = 0.0032. Our study is the most recent, and with the largest cohort, to validate the Melanoma-molGPA score as an accurate and reproducible score for estimating overall survival. As several prospective clinical trials are addressing the issue of optimal therapy including the impact of local treatment for these patients, the Melanoma-molGPA is a useful tool in BM melanoma patients.